2014
DOI: 10.4103/0974-8490.128963
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic effect of saffron (Crocus sativus L.) and its ingredients

Abstract: Conventional and newly emerging treatment procedures such as chemotherapy, catalytic therapy, photodynamic therapy and radiotherapy have not succeeded in reversing the outcome of cancer diseases to any drastic extent, which has led researchers to investigate alternative treatment options. The extensive repertoire of traditional medicinal knowledge systems from various parts of the world are being re-investigated for their healing properties Crocus sativus L., commonly known as saffron, is the raw material for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 46 publications
2
72
0
2
Order By: Relevance
“…In vitro cytotoxicity of saffron on MCF-7 cells is well established by our group and others Mousavi et al, 2011;Bakshi et al, 2012;Nikouei et al, 2013;Samarghandian and Borji, 2014). Further saffron reported for initiation of apoptosis in MCF-7 cells by flow cytometric analysis (Mousavi et al, 2009;Mousavi et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In vitro cytotoxicity of saffron on MCF-7 cells is well established by our group and others Mousavi et al, 2011;Bakshi et al, 2012;Nikouei et al, 2013;Samarghandian and Borji, 2014). Further saffron reported for initiation of apoptosis in MCF-7 cells by flow cytometric analysis (Mousavi et al, 2009;Mousavi et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…We and other reported that C. Sativus and its major constituent crocin is an effective in vitro anti-proliferative agent of MCF-7 cells (Mousavi et al, 2011;Bakshi et al, 2012;Bizhan Malaekeh-Nikouei et al, 2013;Samarghandian and Borji, 2014). Initiation of apoptosis and proportion of MCF-7 cells attained apoptotic state after treatment with saffron has been well enumerated by flow cytometric analysis (Mousavi et al, 2009;Mousavi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Saffron (Crocus sativus L.) is one of the best plant drugs in this group that revives the stomach because of its good smell and astringent quality resulting from soil element dominancy (8,15). Recent studies also showed antidepressant and anticarcinogenic effects of saffron, which are supportive to TPM theories (33)(34)(35)(36). It is so striking that experimental studies approved gastro-protective effect of saffron in GI malignancies (37).…”
Section: Resultsmentioning
confidence: 80%
“…Saffron stigmas contain numerous volatile compounds and ingredients including crocin, picrocrocin and safranal and these compounds are accountable for color, taste and odor of saffron respectively. [8][9][10][11] Safranal is the major coloring constituent of saffron, so saffron is used as a flavoring and coloring agent. 12 In addition to these compounds, saffron also contains little amounts of other pigments like anthocyanin, α-carotene, β-carotene, and zegxantin.…”
Section: Chief Ingredients Of Saffronmentioning
confidence: 99%
“…Stigma ethanolic fraction of saffron showed the highest antioxidant activity that might be recognized due to the presence of phenolics and flavonoids. [3][4][5][6][7][8][9][10][11][12][13][14] Other experimental data advocates that saffron helps in reduction of inflammation through the inhibition of cycoloxygenase enzyme activity. Saffron alleviates neuropathic pain via reduction of proinflammatory cytokines, antioxidant activity and apoptotic pathways 15 and in vitro study has revealed that crocin possess dual inhibitory activity against COX-1 and COX-2 enzymes.…”
Section: Chief Ingredients Of Saffronmentioning
confidence: 99%